Extensive Tinea corporis with photosensivity - Balighi Kamran; Lajevardi Vahide; Barzegar Mohamad; Sadri Majid (Wolters Kluwer Medknow Publications, 2009)
Tinea corporis is a superficial fungal infection of the keratinized epithelial layer, presenting as erythematous scaling patches with central clearing. Sometimes it can resemble other skin disorders, so its misdiagnosis constitutes a problem of considerable practical importance. We describe a patient who presented with widespread Tinea corporis that morphology and distribution of the lesions mimicked lupus erythematosus and/or photodermatosis.